(untitled) (Research, Society and Development, 2021)
The worldwide pandemic caused by the new variant of the Sars-CoV-2 virus, belonging to the Coronaviridae virus family, has spread quickly, showing an alarming scenario for public health. Therefore, restrictive measures were adopted and one of them was social distancing, culminating in the closing of all non-essential activities establishments. Objective: Addressing the occurrence of domestic accidents aimed at children, with the aim of instructing about their levels of prevention. Method: This is an integrative literature review study based on a descriptive analysis, using the deductive hypothetical analysis method. Results: Intra-household accidents that occur due to external causes are mostly 90% preventable, and that can be avoided based on the knowledge of the factors that influence their occurrence. Such as, age, physical, psychic, motor, environmental and sociodemographic influences. It is proven that, as the child matures, their motor development functions, becoming more vulnerable and susceptible to risks. From this, the guidance provided by education with a focus on preventing the occurrence of these situations, can help to reduce rates. Final considerations: The awareness of guardians and caregivers is an important factor to be taken into account, since the prior identification of risk factors is a potential form of prevention.